Isolated steroid-resistant nephrotic syndrome in a Chinese child carrying a de novo mutation in WT1 gene:a case report and literature review - Yiyang Li; Chuan Tian; Yajun Wang; Guoda Ma; Riling Chen (BMC, 2022)
Abstract Background Isolated steroid-resistant nephrotic syndrome (ISRNS) is caused by mutations in the Wilms' tumor-1 (WT1) gene, which encodes glomerular podocytes and podocyte slit diaphragm.We report a novel 8-year-old female patient with ISRNS carrying a de novo missense mutation in WT1 gene and presenting a new type of pathology, have never been reported.We also systematically review previous reports of ISRNS in Chinese children. Case presentation A 8-year-old Chinese patient who had steroid-resistant nephrotic syndrome,responded poorly to immunosuppressant, and had no extrarenal manifestations. The patient had a female phenotype and karyotype of 46, XX. A new type of renal pathology, proliferative sclerosing glomerulonephritis (PSG),and a de novo missense mutation in WT1 gene, c.748C > T (p.R250W),which have not yet been reported, were identified. She was diagnosed with ISRNS.The patient progressed to end-stage renal disease at the age of 10 years,underwent dialysis and kidney transplant. Renal function and urine protein were normal during 4-year follow-up. Conclusions WT1 gene testing should be performed to guide treatment for patients with steroid-resistant nephrotic syndrome, especially for isolated cases and female patients.